Towards a phantom-based quantitative assessment of dose reduction and image-quality trade-offs in half- and full-rotation dental CBCT protocols: a thermoluminescent dosimetry approach with clinical insight - Amasya, Hakan; Gunay, Osman; Kesmezacar, Fahrettin Fatih; Akdogan, Emine Tuna; Kayaokay, Duygu Tuncman; Karacam, Songul Cavdar; Yeyin, Nami; Demir, Mustafa; Orhan, Kaan; ALMisned, Ghada; Tekin, H. O. (SPRINGER, 2026)
This study aimed to compare full- (360 degrees) and half-rotation (180 degrees) dental cone-beam computed tomography (CBCT) protocols in terms of effective dose (ED) and quantitative image quality for the maxilla and mandible regions. An Alderson Radiation Therapy phantom was imaged using a Hyperion X9 Pro (Cefla, Imola) CBCT device with a 10 & times; 6 cm field of view. Both anatomical regions were acquired using full- and half-rotation protocols. A total of 67 thermoluminescence dosimeters were positioned in the phantom for ED calculations. Quantitative image-quality assessment was performed using axial slices extracted from each volume, and signal-to-noise ratio (SNRs) and contrast-to-noise ratio (CNRs) were calculated. The EDs were 406.33 & micro;Sv (full-rotation) and 208.29 & micro;Sv (half-rotation) for the maxilla, and 248.94 & micro;Sv (full-rotation) and 73.63 & micro;Sv (half-rotation) for the mandible. These doses corresponded to dose reductions of 48.74% in the maxilla and 70.42% in the mandible. SNRs and CNRs decreased by 36.69% and 34.74% in the maxilla, and by 49.95% and 50.28% in the mandible, respectively. Dose reduction was more pronounced in the mandible than in the maxilla, and this was accompanied by a greater loss in SNR and CNR. It is concluded that protocol selection should be guided by diagnostic requirements and adherence to the As Low as Diagnostically Acceptable being Indication-oriented and Patient-specific (ALADAIP) principle.
Keywords: Cone-beam computed tomography; Dosimetry, Image quality; Anthropomorphic phantom; Radiographic imaging; Life Sciences & Biomedicine - Other Topics; Biophysics; Environmental Sciences & Ecology; Radiology, Nuclear Medicine & Medical Imaging